Acute immune responses are involved in liver and kidney injury in heat stroke. (April 2019) - Hu, Jie; Kang, Hongjun; Liu, Chao; Yang, Mengmeng; Zhou, Feihu
The changes in circulating cytokines throughout the progression of heat stroke–induced systemic inflammatory response syndrome have been thoroughly described. However, the innate and adaptive immune responses were poorly understood and are explored in this study. A classic heat stroke model in mice was constructed according to the established methods. The time course of splenic T helper cell plasticity, neutrophils, and macrophages in liver and kidney tissues were measured at 0, 24, and 72 h after onset of heat stroke. We showed heat stroke mice presented tachycardia and low mean arterial pressure and exhibited severe kidney and liver injury. Our data demonstrated that heat stroke could increase both the Th17 and Th22 response of splenic T helper cells and incremental infiltration of neutrophils and macrophages into liver and kidney tissues. Moreover, heat stroke could shift those macrophages into the M1 type. This study demonstrates for the first time the increasing splenic T helper response, changes in neutrophil and macrophage infiltration, and macrophage induction in response to heat stroke in mice. Our findings indicate that splenic T helper cells and local neutrophils and macrophages might be potential therapeutic targets for heat stroke.